INTERNALISASI NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN KEMANDIRIAN BERPIKIR KRITIS SISWA DI ERA DIGITAL - Moh. Solehuddin; Mardiana Salma; Laila Fitri Aminah Hasibuan; Ilyas Munawar (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This study examines the role of youth in enhancing the religious awareness of the community in Simpang Duhu Lombang Village, Ulu Pungkut Sub-district, Mandailing Natal Regency. The research is grounded in the notion that youth function as agents of social and religious change, especially within rural communities. Using a qualitative case study approach supported by observation, interviews, and documentation, the study identifies the significant involvement of youth in organizing and promoting religious activities such as Qur’an recitation gatherings, mosque youth programs, and children’s Islamic education. Their initiatives also reinforce Islamic ethics and moral values through socio-religious activities that emphasize solidarity and collective participation. Despite these positive contributions, the study reveals several constraints that limit youth performance, including inadequate facilities, inconsistent public support, and the growing influence of modernization and social media on youth behaviour  To address these challenges, youth employ strategies such as strengthening mosque youth leadership, increasing educational and religious activities, and collaborating with religious leaders to improve program effectiveness. Enhanced collaboration among religious leaders, village authorities, and community members is essential to sustain and expand the youth’s contribution.